anonymous
  • anonymous
6) Write an equation in slope-intercept form of the line through points (-2, 6) and (7, -1). 7) Write an equation in point-slope form for the line that goes through the point (3, -8) and has a slope of -2. Can someone help i dont need anwser i just need help
Geometry
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
chestercat
  • chestercat
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
Have you drawn a quick sketch of the two points on an xy plane?
anonymous
  • anonymous
where are you stuck?
anonymous
  • anonymous
do u knoe formulas

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
(y-y1)/(y2-y1)=(x-x1)/(x2-x1) for first que (y2-y1)=m(x2-x1)
anonymous
  • anonymous
have u got it
anonymous
  • anonymous
Im sorry im so confused
anonymous
  • anonymous
slope=(y2-y1)/(x2-x1) point slope form= y-y1=m(x-x1)
anonymous
  • anonymous
m represents slope
anonymous
  • anonymous
m=(-1-6)/(7+2) m=-7/9 slope is decreasing now put it in point slope form can you?
anonymous
  • anonymous
ohh okay is see how you got that
Hero
  • Hero
(-2, 6) and (7, -1): 6 = -2m + b -1 = 7m + b b = 6 + 2m b = -7m - 1 b = b 6 + 2m = -7m - 1 7m + 2m = -6 - 1 9m = -7 m = -7/9 b = 6 + 2(-7/9) b = 6 -14/9 b = 54/9 - 14/9 b = 40/9 y = -7/9(m) + 40/9

Looking for something else?

Not the answer you are looking for? Search for more explanations.